The magnetoplasma separation method of spent nuclear fuel - Yuferov, V.B.; Shariy, S.V.; Tkachova, T.I.; Katrechko, V.V.; Svichkar, A.S.; Ilichova, V.O.; Shvets, M.O.; Mufel, E.V. (Вопросы атомной науки и техники, 2017)
At present the recycling of nuclear fuel (NF), i.e. its reuse, is implemented by using PUREX-process. However, it leads to increase of liquid radioactive waste (RW) volume, while the alternative methods of physical reprocessing, in particular plasma ones, do not require chemical reagents but use only electrical power. In NSC KIPT it is offered the magnetoplasma reprocessing of spent nuclear fuel (SNF), which includes three stages (heating, ionization, magnetoplasma separation in rotating plasma), on which fission products (FP) are consistently separated from NF. Herewith the simulation of SNF separation should carry out in multicomponent molecular medium. The problems connected with possible presence of complex compounds in SNF and possible ways of their solving are presented. В настоящее время переработка ядерного топлива (ЯТ), т.е. его повторное использование, реализуется с помощью PUREX-процесса. Тем не менее, это приводит к увеличению количества жидких радиоактивных отходов (РАО), в то время как альтернативные методы физической переработки, в частности плазменные, не требуют химических реагентов, а используют только электрическую энергию. В ННЦ ХФТИ предложен магнитоплазменный метод переработки отработанного ядерного топлива (ОЯТ), включающий три стадии (нагрев, ионизация, магнитоплазменное разделение во вращающейся плазме), на которых продукты деления (ПД) последовательно отделяются от ЯТ. При этом моделирование разделения ОЯТ следует проводить в многокомпонентной молекулярной среде. Представлены проблемы, связанные с возможным наличием сложных соединений в ОЯТ, и возможные пути их решения. В даний час переробка ядерного палива (ЯП), тобто його повторне використання, реалізується за допомогою PUREX-процесу. Проте це призводить до збільшення кількості рідких радіоактивних відходів (РАВ), в той час як альтернативні методи фізичної переробки, зокрема плазмові, не вимагають хімічних реагентів, а використовують тільки електричну енергію. У ННЦ ХФТІ запропоновано магнітоплазмовий метод переробки відпрацьованого ядерного палива (ВЯП), що складається з трьох стадій (нагрів, іонізація, магнітоплазмове розділення в плазмі, що обертається), на яких продукти поділу (ПП) послідовно відокремлюються від ЯП. При цьому моделювання сепарації ВЯП слід проводити в багатокомпонентних молекулярних середовищах. Представлено проблеми, що пов'язані з можливою наявністю складних сполук у ВЯП, і можливі шляхи їх вирішення.